Artykuł oryginalnyCorrelation between level of sodium/iodide symporter expression in tissue sections and some clinical parameters in patients with nodular goiter - Syrenicz, Anhelli; Wolny, Małgorzata; Kram, Andrzej; Sworczak, Krzysztof; Syrenicz, Małgorzata; Garanty-Bogacka, Barbara; Walczak, Mieczysław (Archives of Medical Science, 2006)
Introduction: The aim of the study was to correlate the level of NIS expression in hot, warm and cold nodules with some clinical parameters such as TSH, FT3, FT4, TG, TPO-Ab, TG-Ab, TSH-R-Ab in serum samples, iodine in morning urine samples and thyroid volume. Based on these correlations we tried to find clinical factors that interact with NIS expression in benign nodules and at the same time indicators of NIS expression. Material and methods: The study population consisted of 97 people who underwent surgery for toxic nodular goiter (26 people) or non-toxic nodular goiter (71 people). NIS expression was detected by immunohistochemistry on tissue sections of benign nodules and extranodular parenchyma. The level of NIS expression was estimated objectively using a computer program. Results: The study results demonstrated a significant inverse correlation between the level of NIS expression and FT3 in serum samples in the whole study population and in the group of patients with warm nodules who were not treated with thyreostatics. Furthermore, we revealed a significant inverse correlation between the level of NIS expression and serum concentration of TSH-R antibodies in patients with hot nodules. Additionally, a significant inverse correlation between the level of NIS expression and thyroid volume was investigated in the group of patients with nontoxic nodular goiter. Conclusions: Our data indicate the autoregulatory effect of FT3 on NIS expression. Furthermore, it seems that enlargement of thyroid volume in nontoxic nodular goiter coexists with decreased level of NIS expression.